Pathogen introduced to Peru by trade in postlarvae of Litopenaeus vannamei - Guevara, Mervin (2012)
International trade of aquatic animals is the most important source for pathogens introduction in new areas, beginning cause of huge economic losses in growing animals and ecological damage. In this paper, we analyze Litopenaeus vannamei postlarvae imported for shrimp farming companies of Tumbes from Ecuador, in order to detect pathogens such as the white spot virus (WSV), yellow head virus (YHV), infectious hypodermal and haematopoietic necrosis virus (IHHNV), Baculovirus penaei (BP), Taura syndrome virus (TSV) and necrotizing hepatopancreatitis bacterium (NHPB). For this purpose, 177 samples of postlarvae in 2009 and 274 in 2010 from different larviculture laboratories of Ecuador were processed by the technique of PCR. In 2009, four infectious pathogens were present in postlarvae. In 2010 the frequency of occurrence of IHHNV –infected postlarvae was higher (16.79%). Both in 2009 and 2010 were found positive postlarvae NHPB, BP and TSV.